172 The Proprems Randomised Trial Investigating the Effects of Probiotics on Late Onset Sepsis in Very Preterm Infants. (October 2012) - Jacobs, SE; Tobin, JM; Opie, G; Donath, S; Pirotta, M; Tabrizi, SN; Morley, CJ; Garland, SM
Abstract : Background: Late onset sepsis (LOS) frequently complicates prematurity, and is associated with increased mortality and morbidity. Whilst probiotic supplementation in preterm infants reduces mortality and necrotising enterocolitis (NEC), the effect on LOS in the most vulnerable preterms is unknown. Aim: To determine the effects of probiotic supplementation in very preterm infants. Methods: A multi-centred, double-blinded, placebo-controlled, randomised controlled trial in very preterm infants born < 32 weeks' gestation weighing < 1500g, supplemented daily with either a probiotic combination ( Bifidobacterium infantis, Streptococcus thermophiles and Bifidobacterium lactis 1 x 10 9 total organisms) or placebo (multodextrin) from soon after commencement of enteral feeds until discharge home or term corrected age. The primary outcome was the incidence of at least one episode of definite (deep culture positive) late onset sepsis; secondary outcomes included NEC, mortality, duration of primary hospitalisation, number of courses and duration of antibiotics, etc. [Garland et al. BMC Infectious Diseases . 2011 Aug 4; 11(1):210]. Results: Between October 2007 and November 2011, 1099 very preterm infants were randomised from 10 participating perinatal centres in Australia and New Zealand. Four interim analyses at 100, 200, 350 and 700 recruits confirmed comparable baseline characteristics between groups (for birth weight, gestation, gender, multiple pregnancy, antenatal steroids, caesarean delivery) and recommended trial continuation. Data cleaning is nearing completion prior to unblinding treatment allocation groups and analysis. Conclusions: The ProPrems trial has recruited 1099 very preterm infants; it is the largest randomised trial to date investigating the potential for probiotics to reduce the burden of prematurity.